Maternal Satisfaction towards Childhood Immunization Service and Its Associated Factors in Wadla District, North Wollo, Ethiopia, 2019 - Fisha Alebel GebreEyesus; Nega Tezera Assimamaw; Netsanet Tsegaye GebereEgziabher; Bisrat Zeleke Shiferaw (International Journal of Pediatrics)
Background. Maternal satisfaction is considered one of the most frequently used indicators to measure the quality and efficiency of childhood immunization service. Evaluating maternal satisfaction towards childhood immunization service is very relevant as it likely affects the clinical and revisit adherence, service quality, and its coverage. In countries like Ethiopia, where childhood immunization coverage is below average (39%) with low maternal satisfaction on the service, identifying factors associated with maternal satisfaction is very critical. Despite the acknowledgement made on the importance of maternal satisfaction for the successful provision of child immunization services, there is limited knowledge in Ethiopia on its contributing factors. Objective. The aim of this study was to assess maternal satisfaction towards childhood immunization service and its associated factors among mothers’ having children aged less than 1 year in Wadla district, North Wollo, Ethiopia, 2019. Methods. A community-based cross-sectional study was conducted among 682 mothers from March to April 2019 in Wadla district, North Wollo, Ethiopia. A two-stage cluster sampling technique was used to select households of the study participants. A pretested interviewer-administered structured questionnaire was used. During the period of data collection, every questionnaire was cross-checked and the collected data were checked for completeness and consistency on a daily basis. Then, the cleaned data was coded and entered in to Epi Info software version 7.2.2.2 and exported to SPSS software version 23.0 for analysis. Bivariable and multivariable logistic regression analysies were done to identify variables having a significant association with maternal satisfaction. Variables with a p value of ≤ 0.05 and adjusted odds ratio with 95% CI were considered having a statistically significant association during multivariable logistic regression analysis. Then, the findings were presented using tables, graphs, and charts. Result. The overall proportion of maternal satisfaction towards childhood immunization service was found to be 68.2% [95%CI=64.7%−71.7%]. The finding revealed that attending secondary education [adjusted odds ratio AOR=0.26; 95%CI=0.13−0.53], being divorced [AOR=0.46; 95%CI=0.23−0.91], and having favorable attitude towards child immunization [AOR=1.58; 95%CI=1.05–2.33] were found to be significantly associated with maternal satisfaction. Furthermore, the multivariable logistic regression analysis showed that short waiting time before receiving service [AOR=1.83; 95%CI=1.21−2.79], greeting from care providers, [AOR=5.69; 95%CI=3.36−9.65], having information about the current vaccine [AOR=2.03; 95%CI=1.25−3.32], dose of vaccine [AOR=2.24; 95%CI=1.40−3.58], and next immunization schedule [AOR=3.21; 95%CI=1.70−6.04] were also significantly associated with maternal satisfaction towards childhood immunization services. Conclusion and Recommendation. Generally, the study showed that more than two-thirds of the mothers were satisfied by the immunization service rendered. The level of satisfaction was higher with respect to the health workers’ relationship, communication, and immunization system aspects. However, more efforts need to be put towards improving the service waiting time for immunization, and provision of health information and communication is also recommended to enhance the level of favorable attitude among mothers towards childhood immunization services.